India Transport Report Volume III Sector Reports Part I - Planning Commission (Planning Commission, 2013)
It is rightly referred to as ‘the lifeline of the Indian economy’ as it facilitates industrial and economic development by transporting materials such as coal, iron ore, fertilisers and food grains. It touches the lives of people in both tiny villages and urban metropolises and assists the evolution of social forces like urbanisation and inclusive development.
Moving India To 2032
National Transport Development Policy Committee